The impact of motivation on language learning - Al Ali, Batool Dahham (Research Journal in Advanced Humanities, 2026)
In every classroom, there are some students who are unmotivated to learn. One school in Basra, South Iraq is no exception.  Some students are academically failing and many educators believe that motivation is not the solution. Previous studies have discussed two concepts of motivation that inspire students to learn namely; intrinsic and extrinsic which are used in this study, in addition to several process theories of motivation such as: Maslow’s Hierarchy of Needs, Vroom’s theory of expectancy, and the Incentive Theory of Motivation. This study aims at finding out if both forms of motivation, intrinsic and extrinsic, are needed to help EFL students at a school in build their self-confidence which leads to increased participation levels, higher grades, and consequently academic success. The participants are all the students in three sections of Grade 8 (age 13-14 years). Students in the first section were motivated extrinsically using rewards, medals, surprises, praise, and gifts. Students in the second section were motivated intrinsically through using activities, curiosity-aroused tasks, games, plans of actions, and examples from daily life. Students in the third section were motivated intrinsically and extrinsically using medals, rewards, gifts, praise, and surprises as well as activities, curiosity-aroused tasks, games, plans of actions, and examples from daily life. The data results were analyzed quantitatively and were divided into two parts, first and second term data results, and third term data results. The researcher employed a questionnaire to collect data from 70 participants in order to measure their motivation level, confidence level, and participation level in the classroom before the motivation process, during the process, and after it in addition to observing the students participation in the classroom. The effects of intrinsic and extrinsic motivation were evaluated by comparing responses to the questions that were asked in the three terms and by comparing grades of the first, second, and the third test of each student. The questionnaires, observation scores, and test results were data collection methods of the study. Findings revealed that the two concepts of motivation had a considerable impact on the self-confidence of students, participation level, and their academic results and revealed that students who were motivated extrinsically and intrinsically scored better on the reading and writing exams than the students who were only motivated extrinsically. Furthermore, there were several limitations on this study including the small sample size chosen and the undermining of individual factors of students such as backgrounds and critical thinking. As for future expectations, it is recommended to conduct further research studies supplementing this quantitative analysis with qualitative evidence that analyzes issues related to the effects of motivation on self-confidence, participation, and academic success, for example, conducting in-depth interviews with a number of participants.